Efektivitas Pembelajaran Menyimak Dongeng Berbasis Youtube Dalam Pembelajaran Bahasa Sunda Pada Masa Pandemi Covid-19 - Ramadan, Edwin; Triwahyuni, Heti (Jurnal Sains Indonesia, 2020)
This study has a background in the lack of knowledge of students in listening to fairy tales at SMPN 1 Cilimus, Kuningan District. Therefore this study aims to examine the ability of students to listen to fairy tales (1) the effectiveness of YouTube media in learning Sundanese during the co-19 pandemic (2). This study uses a quantitative approach. The method used is an experimental method with pretest and posttest design. The source of the data in this research is the class VII students of SMPN 1 Cilimus, Kuningan Regency with a total of 32 students. The results of the study were an increase in the ability of students to listen to fairy tales using youtube. The ability of students before using YouTube media is 9.37%, while after using YouTube media it becomes 34.38%. In addition, the increased ability to listen to fairy tales can be seen from the results of hypothesis testing which shows tcount 0.2862> t table 2,384. That is, there are significant differences between learning outcomes before and after using YouTube media. Keywords: Sundanese learning, youtube, listening to fairy tales.